Understanding data communications from fundamentals to networking - Held, Gilbert (John Wiley & Sons, 1997)
This expanded and completely updated edition, of the popular text reflects the major changes to communications technology since 1990. New coverage includes discussions of ATM and Frame Relay, Ethernet and Token-Ring Networks, and expanded treatment of satellite communications. There is also new material on the ATM LAN versus WAN evolution as well as new sections on LAN networking and Internetworking. Emphasis is given throughout to reflect the emergence of the Internet with timely information on TCP/IP, NetWare, and LAN applications.